The effects of micro-fracture on the structural responses of concrete - Yip, Woon kwong. (2011)
A body of concrete in a structure which has experienced load history would have sustained certain degree of micro-fracture damage, and hence its constitutive state would have being altered. Diagnostic appraisal of such a structure investigates the ability of the in-place concrete to sustain further loading. Strengthening of such concrete can be carried out to rehabilitate its load carrying capacity.